Silent period in carpal tunnel syndrome - Resende, Luiz Antonio de Lima [UNESP]; Alves, R. P.; Castro, H. A L; Kimaid, P. A T [UNESP]; Fortinguerra, C. R H; Schelp, Arthur Oscar [UNESP] (My University, 2000)
The silent period is a misunderstood electrophysiological phenomenon leading to several different hypotheses explaining its electrogenesis. It has been studied by different authors and different methodologies giving a wide variability of results, therefore an exact pattern of its normal values does not exist. This work was undertaken to define the normal morphology and duration of the silent period obtained by supramaximal stimulus of the median nerve, during maximum isometric effort of the abductor pollicis brevis muscle against resistance, using 20 adult volunteers without neurological alterations. The normal median duration was 104.6 milliseconds. The same methodology was applied to 20 hands from 20 patients with carpal tunnel syndrome. The silent period showed many types of morphological alterations, but the major alteration observed was a tendency to temporal elongation. No correlation between the severity of the carpal tunnel syndrome and the silent period alterations were observed.
Keywords: Carpal tunnel syndrome; Silent period; adult; aged; carpal tunnel syndrome; clinical article; controlled study; electromyography; female; human; impedance; male; mechanical stimulation; muscle isometric contraction; nerve conduction; nervous system electrophysiology; time perception; waveform; Adult; Aged; Carpal Tunnel Syndrome; Electric Stimulation; Electromyography; Evoked Potentials; Female; Humans; Isometric Contraction; Male; Median Nerve; Middle Aged; Motor Neurons; Muscle, Skeletal; Neural Conduction; Neurons, Afferent; Reaction Time; Thumb; Time Factors